Peningkatan kemampuan menganalisis sifat-sifat cahaya melalui model predict observe explain peserta didik kelas V sekolah dasar - Yulistari, Silviana; Kurniawan, Sandra Bayu; Yulianti, Yulianti (Universitas Sebelas Maret, 2019)
Abstract. The aim of this study was to improve the ability to analyze the properties of light using the Predict Observe Explain learning model in fifth grade students of Totosari Elementary School No.102 Surakarta 2018/2019. This research was performed as classroom action research (CAR) were carried in two cycles. The research subjects were teacher and fifth grade students of Totosari Elementary School No.102 Surakarta, totaling 32 students. Observation, interviews, documentation, and tests were used as data collection techniques. The data validity used were triangulation source and technical triangulation. The data were analyze by an interactive analysis model. The results of this classroom action research show that the class average score in the pre-action is 45.20 with the class achievement percentage of 0%. In the first cycle, the average score of the class increased up to 65.41 with percentage of class achievement of 31.25%. In the second cycle, the average score of the class increased up to 81.35 with percentage of class achievement of 84.38%. The conclusion of this study showed that through the Predict Observe Explain (POE) learning model can improve the ability to analyze the properties of light in fifth grade students of Totosari Elementary School No.102 Surakarta 2018/2019.Keyword: Analysis Ability, Properties of Light, Predict Observe Explain (POE)